Influence of cooking methods on bioactive compounds in beetroot - Juliana Arruda Ramos (Semina: Ciências Agrárias, 2017)
Beetroot is rich in bioactive compounds that may provide health bene¿ts. However, vegetable tissues are physically and chemically damaged by cooking, causing major changes to compounds in cell membranes. The current study aimed to evaluate the inÀuence of several cooking methods on bioactive compounds in beetroot. Four heat treatments were carried out: steam cooking, pressure cooking, baking in an oven, and boiling in water. Beets were matched in uniformity of size, color, and absence of defects. They were washed thoroughly in running water to remove dirt. Next, one of the four cooking methods was applied. After cooking, beets were peeled by hand. Analysis was carried out on both uncooked and cooked beets to evaluate antioxidant activity, content of phenolic compounds, pigments, Àavonoids, and betalains. The experiment was completely randomized design (CRD) and carried out in triplicate. Data were subjected to analysis of variance (F test, p < 0.05) and mean values compared by Tukey test at 5% probability. There was no change in antioxidant activity or total phenolic and anthocyanin content by any of the cooking methods compared to that in raw beetroots. However, pressure-cooking resulted in lower carotenoid levels compared to that in raw beet. Furthermore, Àavonoid and betalain content decreased by all the cooking methods.